What labour market? A critical STEM supply shortage investigation: Lithuanian case - Vaitekaitis, Jogaila (Journal of Education Culture and Society, 2020)
Aim. The main objective of this investigation is to explore perceived lack of Lithuanian STEM labour force supply. It is often believed that education systems are the bottleneck of economic growth and that by increasing the supply of STEM (science, technology, engineering, mathematics) graduates we will get more and better payed jobs. But a growing body of evidence suggests that in many STEM fields there is an adequate supply or even oversupply of STEM majors. Still, technologically advanced capitalist countries advocate for more STEM workforce regardless of an overcrowded market. Echoing foreign neoliberal trends, Lithuanian education policy makers are on the same STEM shortage hype-train, and reforms are full steam ahead.Methods. To explore perceived lack of Lithuanian STEM labour force supply an assessment of STEM graduates’ (n=3720) occupational destinations one year after graduation and average salaries in those professions was conducted employing a descriptive statistical analysis.Results. Findings show that there is no general shortage of STEM labour supply; the majority (54% n=2023) of all recent STEM degree holders in Lithuania do not work in STEM jobs. The majority of graduates usually do not reach national average income one year after graduation.Conclusions. Persuasion of students to study STEM degrees based on better labour market outcomes is misleading and possibly unethical. The principal theoretical implication of this paper is the acknowledgment that low STEM graduate employment does not necessarily signify a failing education system. Rather, this is an opportunity to look beyond human capital and labour market discourse which, arguably, prevents STEM education to realize its revolutionary potential.